(untitled) (Research, Society and Development, 2022)
High power surgical lasers are indicated for soft tissue surgeries of the oral cavity, such as frenectomy, which consists of the complete removal of the buccal or lingual frenulum. Objective: This integrative review aims to punctuate the types of surgical lasers, and the benefits and limitations of their use in the removal of frenulum. Methodology: Search and analysis of articles, in English, Spanish and Portuguese, indexed from 2016 to 2022, in the digital databases LILACS, PubMed, BBO, Cochrane, MEDLINE and SciELO using the descriptors “laser”, “frenectomy” and “oral surgery” with the AND association. This methodology followed the PRISMA recommendations (Key Items for Reporting Systematic Reviews and Meta-analysis), adapted for integrative review. Results: The search generated 57 articles, after inclusion and exclusion criteria, 20 articles of the literature review, systematic review, qualitative study, randomized study, case report, clinical study and meta-analysis were selected. Conclusion: Regarding the benefits of these mechanisms, the reduction in surgical time, greater cutting precision, less bleeding and pain, faster healing and greater comfort in the postoperative period, as there is no need for suture. As for the limitations highlighted, they would be the little discussion and clinical experience of the use of surgical lasers in general, and their high cost for acquisition and maintenance, which limits public and private institutions and services to acquire them. They also emphasize the need and incentive for clinical research with these equipment and focusing on this theme, as all the lasers discussed present satisfactory results, especially in the postoperative period.